Fabricating Tissues In Situ with the Controlled Cellular Alignments (Adv. Healthcare Mater. 3/2022). Issue 3 (2nd February 2022) - He, Chuanjiang; Liu, Mengxue; Jiang, Deming; Wu, Jianguo; Qin, Chunlian; Liang, Tao; Wu, Pan; Han, Chunmao; Huang, Liquan; Hsia, K. Jimmy; Wang, Ping
Abstract : Cellular Alignment In article number 2100934, K. Jimmy Hsia, Ping Wang, and co‐workers report a method of fabricating engineered tissues in situ with the controlled cellular arrangements. By integrating the "stretch" and "adhere" steps into the fabricating process, a static mechanical environment can be created, which would regulate the subsequent cellular alignment, elongation, and differentiation in the generated physiologically relevant tissues.